The effect of multi-walled carbon nanotubes-additive in physicochemical property of rice brand methyl ester: Optimization analysis - Kusumo F.; Mahlia T.M.I.; Shamsuddin A.H.; Ong H.C.; Ahmad A.R.; Ismail Z.; Ong Z.C.; Silitonga A.S. (MDPI AG, 2023)
Additives; Alternative fuels; Biodiesel; Blending; Calorific value; Diesel engines; Diesel fuels; Esters; Fuel additives; Mean square error; Nanotubes; Neural networks; Oils and fats; Optimization; Physicochemical properties; Surface properties; Average absolute deviation; Correlation coefficient; Flight optimization; Mean absolute percentage error; Optimization analysis; Response surface methodology; Rice brans; Root mean square errors; Multiwalled carbon nanotubes (MWCN)